Exploring the patriarchal limits of liberal democracy. Spanish feminist movement’s shift from institutional to protest struggle - Romero Portillo, Daniel; Márquez Bono, Laura (FEMERIS: Revista Multidisciplinar de Estudios de Género, 2021)
8th of March protests have recently become one of the most salient political phenomena. In Spain, the rate of participation and the nature of its demands clearly depict a strong and organized movement highly critical of how the democratic regime itself serves women interests and needs. Thus, after reviewing how feminist theory have previously dealt with liberal democracy theory and its concept of citizenship, it is explored whether Spanish feminist movement supports or not liberal democracy. To accomplish that goal, statistical analysis is developed using data from opinion barometers 3173 (April 2017) and 3210 (April 2018) by Spanish Center for Sociological Research (CIS). Descriptive graphics and regression models are used to test the hypothesis. Strong evidence is found on the relationship between the increase of protest politics and feminist ideologization, especially among young women. Meanwhile, slighter but actual evidence is found on whether participating in feminist protests leads to either non-institutional feminist electoral alternative or abstention, depending on self-political effectiveness. Hence, the increase in political strength on the Spanish feminist movement has not implied a disengagement of liberal democracy although grievances and obstacles to participation this political system impose to women. Instead, it has led to a struggle for radical democracy supported by feminist disregarding age or left-right ideological self-placement